Sedimento en el contenido estomacal de Mugil cephalus y Mugil curema (Mugiliformes: Mugilidae) en laguna de Tamiahua, México - Sánchez Rueda, Patricia (1997)
The granulometric composition and the most important inorganic componente of sediments in the stomach of two mullet species (Mugil cephalus and Mugil curema) were sampled m Tamiahua lagoon, Veracruz, Mexico. M. cephalus is characterized by the presence of fine sand to medium silt, with diameters of 125 to 15 m with preference for fine sand of 63 m. M. curema presented an interval of fine sand from 125 m to coarser silt of 32 m of thickness with preference for the latter. Presence of fine particles probably is related with diatom abundance in the stomach of both species: diatoms are the main nutritional source. The granulometric differences of the two species suggest competitive exclusion.